Cluny and the Muslims of La Garde-Freinet : hagiography and the problem of Islam in Medieval Europe - Bruce, Scott G. (Scott Gordon), 1967- (Cornell University Press, 2015)
In the summer of 972 a group of Muslim brigands based in the south of France abducted the abbot of Cluny as he and his entourage crossed the Alps. Ultimately, the abbot was set free and returned home safely, but the abduction outraged Christian leaders and galvanized the will of local lords. Shortly thereafter, Count William of Arles marshaled an army and succeeded in wiping out the Muslim stronghold. This book uses this incident to examine Christian perceptions of Islam in the Middle Ages.